Influence of learning objects in the implementation of the flipped classroom (Revista Innova Educación, 2022)
This article aims to present a systematic review of the literature that addresses the methodological implementation of the flipped classroom and its relationship with the different learning objects used in this interactive space. From this review, it was investigated the use of these objects in the classroom with the motivation and academic performance of the students. The methodology used in this study was the documentary review of 30 articles published in different scientific databases. Studies were analyzed in the period between 2015 and 2020, which allowed concluding the application of different learning objects simultaneously had a positive influence on student motivation. It should be further clarified academic performance tends to increase applied learning objects indistinctly.
Keywords: flipped learning; flipped classroom; students; motivation; learning objects; critical thinking